Penggunaan Lirik Lagu “Bertaut” Karya Nadin Amizah dalam Keterampilan Menulis Puisi Bertemakan Ibu - Iqbal, Muhamad Nur (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2023)
This research aims to determine the use of the lyrics of the song "Bertaut" by Nadin Amizah in the skills of writing mother-themed poetry in class X MIPA 2 SMA Negeri 1 Ciseeng Bogor academic year 2021/2022. The method used in this research is a qualitative descriptive method. Data collection techniques in this research are observation, interviews, tests and documentation. The aspects assessed in poetry writing skills are suitability of theme and meaning, strength of imagination, accuracy of diction, and use of figures of speech and imagery. The results of this research show that the use of the lyrics of the song "Bertaut" by Nadin Amizah in poetry writing skills with the theme of students' mothers at SMA Negeri 1 Ciseeng Bogor for the 2021/2022 academic year received a good response from teachers and students because it was able to become a learning innovation and was able to stimulate students in Learning Activities. This can be proven by the fact that 10 or 28% of students obtained grades in the very good category. The results of the recapitulation of post-test scores show that students obtained an average score of 79.71. Meanwhile, before using song lyrics media, it showed that students only got an average score of 59.85.   Penelitian ini bertujuan untuk mengetahui penggunaan lirik lagu “Bertaut” karya Nadin Amizah dalam keterampilan menulis puisi bertemakan ibu pada siswa kelas X MIPA 2 SMA Negeri 1 Ciseeng Bogor Tahun Pelajaran 2021/2022. Metode yang digunakan pada penelitian ini adalah metode deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, tes dan dokumentasi. Aspek yang dinilai dalam keterampilan menulis puisi adalah kesesuaian tema dan makna, kekuatan imajinasi, ketepatan diksi, dan pendayaan majas dan citraan. Hasil penelitian ini menunjukkan bahwa penggunaan lirik lagu “Bertaut” Karya Nadin Amizah dalam keterampilan menulis puisi bertemakan ibu siswa pada SMA Negeri 1 Ciseeng Bogor Tahun Pelajaran 2021/2022 mendapat respons yang baik bagi guru dan siswa karena mampu menjadi inovasi pembelajaran dan mampu menstimulus siswa dalam kegiatan pembelajaran. Hal tersebut dapat dibuktikan dengan terdapatnya 10 atau 28% siswa memperoleh nilai dengan kategori baik sekali. Hasil rekapitulasi nilai post-test menunjukan peserta didik memperoleh nilai dengan rata-rata 79,71. Sementara sebelum menggunakan media lirik lagu, menunjukan peserta didik hanya memperoleh nilai dengan rata-rata 59,85.